Composite lithium supplementing material and preparation method thereof, positive electrode material and secondary battery
By using modified ligands in composite lithium supplement materials to control particle size, the problem of excessive particle size and uneven distribution of material is solved, and the performance and safety of the battery are improved.
Patent Information
- Application Number
- CN202411758420.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
AI Technical Summary
The particle size of the composite lithium supplement material is too large and unevenly distributed, resulting in a degradation of battery performance and affecting the consistency and safety of the battery.
By combining modified ligands on lithium-rich materials and functional materials, the agglomeration phenomenon of materials is reduced, the particle size is controlled, and the particle size distribution is evenly distributed.
The electrochemical performance of composite lithium supplement material is optimized, the torsion of the electrode sheet is reduced, and the magnification and cycling performance of the material are improved.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery. Background Art
[0002] During the initial charge and discharge process of a lithium-ion battery, a large amount of solid electrolyte interface film will be generated on the surface of the negative electrode of the battery, which consumes the limited lithium ions and electrolyte in the battery, causing irreversible capacity loss, reducing the energy density of the lithium-ion secondary battery and the charge and discharge efficiency of the electrode material, limiting the application of lithium-ion batteries. In the prior art, the first irreversible capacity loss of a lithium battery can be effectively compensated by adding lithium-rich materials to the positive electrode material.
[0003] However, due to the problem of adapting the charging voltage platform of the lithium-rich material and the charging voltage platform of the positive electrode active material, some lithium-rich materials with high charging voltage in the prior art need to be combined with a catalyst to reduce the charging voltage platform. Therefore, in the process of preparing the lithium-rich material, it will be compounded with the catalyst, and in order to improve the catalytic effect, more catalysts will be agglomerated on the lithium-rich material, which will inevitably increase the particle size of the obtained composite lithium-supplementing material. As a result, the problem of the composite lithium-supplementing material being too large and unevenly distributed is ignored, which will lead to the situation that the slurry fineness is too large and stripes appear in the process of preparing the pole piece, or the coating on the positive electrode is uneven due to the uneven distribution of the particle size, resulting in excessive tortuosity, which will have an adverse effect on the consistency and even safety of the battery. At the same time, the composite lithium-supplementing material with too large a particle size will also affect the dissolution and diffusion efficiency of the lithium-rich material, thereby reducing its lithium-supplementing performance. Summary of the invention
[0004] The purpose of the present application is to provide a composite lithium supplement material and a preparation method thereof, a positive electrode material and a secondary battery, so as to solve the problem that the composite lithium supplement material has an excessively large particle size and uneven distribution, thereby affecting the battery performance.
[0005] To achieve the purpose of this application, this application provides the following technical solutions:
[0006] In a first aspect, the present application provides a composite lithium supplement material, comprising a lithium-rich material and a functional material, wherein the surface of at least one of the lithium-rich material and the functional material has a modified ligand, and the lithium-rich material and the functional material are connected via the modified ligand.
[0007] In one embodiment, the functional material includes a carbon material and a catalyst, the carbon material has a first modified ligand on its surface, and the catalyst is connected to the first modified ligand to form a complex.
[0008] In one embodiment, the surface of the lithium-rich material has a second modifying ligand, and the first modifying ligand and the second modifying ligand cooperate to connect the lithium-rich material and the carbon material.
[0009] In one embodiment, the first modifying ligand comprises a first functional group ligand and / or a non-carbon heteroatom ligand, and the second modifying ligand comprises a second functional group ligand.
[0010] In one embodiment, the second functional group ligand includes one or more of a carboxyl group, a hydroxyl group, and an amine group, the heteroatom ligand includes one or more of a phosphorus atom, a sulfur atom, and a nitrogen atom, and the second functional group ligand includes an ester group -COOR1 and / or an amide group -CO-NH-R2, wherein R1 includes an alkyl group or other non-hydrogen group, and R2 includes an alkane or other substituent.
[0011] In one embodiment, the particle size D50 of the carbon material is 0.5 μm to 1.0 μm.
[0012] In one embodiment, the tap density of the carbon material is 1.5 g / cm 3 ~3.0g / cm 3 .
[0013] In one embodiment, the particle size D50 of the catalyst is 0.2 μm to 1.2 μm.
[0014] In one embodiment, the catalyst has a tap density of 1.0 g / cm 3 ~4.5g / cm 3 .
[0015] In one embodiment, the carbon material includes one or more of Ketjen black, carbon black, carbon nanotubes, and carbon fibers.
[0016] In one embodiment, the catalyst includes one or more of metal oxides, metal carbides, and metal sulfides.
[0017] In one embodiment, the particle size D50 of the lithium-rich material is 0.05 μm to 1.2 μm.
[0018] In one embodiment, the tap density of the lithium-rich material is 1.0 g / cm 3 ~8.5g / cm 3 .
[0019] In one embodiment, the mass fraction of the functional material in the composite lithium supplementing material is 5% to 30%.
[0020] In one embodiment, the particle size D50 of the composite lithium supplement material is 0.5 μm to 2 μm.
[0021] In one embodiment, the particle size D99 of the composite lithium supplement material is less than or equal to 15 μm.
[0022] In a second aspect, the present application provides a method for preparing a composite lithium-supplementing material, comprising: mixing a lithium-rich material and a functional material together to obtain a mixed liquid, wherein the surface of at least one of the lithium-rich material and the functional material has a modified ligand; adding the mixed liquid to an organic solvent and stirring to precipitate a solid, washing and drying the solid to obtain the composite lithium-supplementing material, wherein the lithium-rich material and the functional material are connected via the modified ligand.
[0023] In one embodiment, before mixing the lithium-rich material with a modified ligand and the functional material together, the process includes: using a surface modifier to modify the surface of the carbon material to obtain a carbon material with a first modified ligand; mixing the carbon material with the first modified ligand and a catalyst for reaction, and washing and drying after the reaction to obtain the functional material.
[0024] In a third aspect, the present application provides a secondary battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the composite lithium supplement material as described in the first aspect.
[0025] In one embodiment, the porosity of the positive electrode sheet is 30% to 45%.
[0026] In one embodiment, the tortuosity of the positive electrode plate is 1 to 2.5.
[0027] In one embodiment, the powder shedding rate of the positive electrode is less than or equal to 0.02%.
[0028] In one embodiment, the electrode sheet peeling strength of the positive electrode is greater than or equal to 6N / 10mm.
[0029] The present invention combines modified ligands on both the lithium-rich material and the functional material. The modified ligands can reduce the agglomeration of the lithium-rich material itself, and can also reduce the agglomeration of the functional material itself, so as to control the particle size of the lithium-rich material and the functional material, so that the overall particle size distribution of the lithium-rich material and the functional material is uniform, and the electrochemical performance of the composite lithium-supplementing material can be optimized. The composite lithium-supplementing material is more evenly coated during application, thereby greatly reducing the tortuosity of the pole piece, which is beneficial to the improvement of the material's rate and cycle performance; at the same time, the lithium-rich material and the functional material are connected by the modified ligand, and the conductivity and catalytic property of the functional material are utilized to improve the conductivity of the composite lithium-supplementing material and effectively reduce the charging voltage platform of the lithium-rich material. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0031] Figure 1 is a schematic cross-sectional view of a composite lithium supplement material according to an embodiment;
[0032] Figure 2 is a cross-sectional schematic diagram of a composite lithium supplement material according to another embodiment;
[0033] Figure 3 The present invention is a flow chart of a method for preparing a composite lithium supplement material according to an embodiment of the present invention;
[0034] Figure 4 is a flow chart of a method for preparing a functional material in one embodiment;
[0035] Figure 5 The present invention is a flow chart of a method for preparing lithium-rich materials according to an embodiment of the present invention. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0037] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.
[0038] It should be noted that the "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0039] All steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b, etc.
[0040] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0041] The following is an explanation of the names that appear in the text:
[0042] Particle size D50: The particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 50%. Its physical meaning is that particles with a particle size larger than it account for 50%, and particles with a particle size smaller than it also account for 50%. D50 is also called the median diameter or median particle size.
[0043] Particle size D99: The particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 99%. Its physical meaning is that particles with a particle size smaller than it account for 99%. D99 is also called the peak particle size.
[0044] Complex: A class of compounds with a characteristic chemical structure, formed by a central atom (or ion, collectively referred to as the central atom) and the molecules or ions surrounding it (called ligands / ligands) fully or partially bonded through coordination bonds.
[0045] Slurry fineness: refers to the degree of dispersion of granular materials in the slurry, usually refers to the size and distribution of solid particles in the slurry. It reflects the degree of refinement and uniformity of the particles in the slurry.
[0046] Tortuousness: describes the ratio between the actual path of particles or ions moving in a porous medium, such as the electrode of a lithium-ion battery, and the shortest straight-line distance. The larger the ratio, the more tortuous the path, which affects the migration speed and efficiency of the ions.
[0047] Pole sheet porosity: Pole sheet porosity refers to the volume fraction of pores in the electrode coating and is one of the important indicators for evaluating the performance of lithium-ion batteries.
[0048] This application provides a composite lithium supplement material, please refer to Figure 1 and Figure 2 .
[0049] In one embodiment, the composite lithium supplement material includes a lithium-rich material 10 and a functional material 20, at least one of the lithium-rich material 10 and the functional material 20 has a modified ligand on its surface, and the lithium-rich material 10 and the functional material 20 are connected via the modified ligand.
[0050] The present invention combines modified ligands on both the lithium-rich material 10 and the functional material 20. The modified ligands can reduce the agglomeration of the lithium-rich material 10 itself, and can also reduce the agglomeration of the functional material 20 itself, so as to control the particle size of the lithium-rich material 10 and the functional material 20, so that the overall particle size distribution of the lithium-rich material 10 and the functional material 20 is uniform, which can optimize the electrochemical properties of the composite lithium-supplementing material. The composite lithium-supplementing material is more evenly coated during application, thereby greatly reducing the tortuosity of the electrode piece, which is beneficial to the improvement of the material's rate and cycle performance. At the same time, the lithium-rich material 10 and the functional material 20 are connected by the modified ligands, and the conductivity and catalytic properties of the functional material 20 are utilized to improve the conductivity of the composite lithium-supplementing material and effectively reduce the charging voltage platform of the lithium-rich material 10.
[0051] In one embodiment, the lithium-rich material 10 is used for lithium supplementation. The lithium-rich material 10 can be granular, including spherical or quasi-spherical. By binding a modifying ligand to the lithium-rich material 10, the lithium-rich material 10 can be controlled to be primary particles, which helps to better solve the problem of the too large particle size of the lithium-rich material 10, thereby improving the performance of the lithium-rich material. During the first charging process, lithium (Li) in the lithium-rich material 10 can be released and migrate to the negative electrode of the battery to offset the irreversible lithium loss caused by the formation of the SEI film, improving the total capacity and energy density of the battery.
[0052] In one embodiment, the chemical formula of the lithium-rich material 10 includes Li x1 C y1 O z1 , where 0 < x1 ≤ 2, y1 > 0, z1 > 0. In a specific embodiment, the lithium-rich material 10 may include Li 2 C 2 O 4 (lithium oxalate), Li 2 CO 3 (lithium carbonate), Li 2 C 3 O 3 (lithium trimesate), Li 2 C 4 O 4 (lithium butynedioate), Li 2 C 6 O 6 , Li 2 C 3 O 5 (lithium pyruvate), and Li 2 C 4 O 6 or one or more of them.
[0053] In one embodiment, the chemical formula of the lithium-rich material 10 includes Li x2 M y2 O z2 , where M is at least one element among Fe, Ni, Mn, Cu, Zn, Co, Cr, Zr, Sb, Ti, V, Mo, Sn, etc., 1 ≤ x2 ≤ 8, 0 < y2, 0 < z2 < 7. In a specific embodiment, the lithium-rich material 10 may include Li 5 FeO 4 , Li 6 MnO 4 , Li 6 CoO 4 , Li 6 ZnO 4 , Li 2 NiO 2 , Li 2 CuO2 , Li 2 CoO 2 , Li 2 MnO 2 , Li 2 Ni 0.5 Mn 1.5 O 4 , Li 2 Ni d Cu (1-d) O 2 (0 < d < 1), etc., at least one of them.
[0054] In one embodiment, the chemical formula of the lithium-rich material 10 includes Li 1+x3 A y3 O z3 , where 0 < x3 ≤ 1.2, 1 ≤ y3 < 3, z3 > 0, and A includes at least one of Ni, Fe, Mn, Co, Cr, V, Mo, Ti, Nb, Zr, Cu, Mg. These lithium-rich materials 10 can be used as a lithium supplement agent or directly as a cathode material. Exemplarily, the lithium-rich material 10 includes Li 2 CuO 2 , Li 2 NiO 2 , Li 2 MnO 2 , at least one of them.
[0055] In one embodiment, the lithium-rich material 10 can also include LiOH (lithium deintercalation potential 4.8V), Li 4 SiO 4 (lithium deintercalation potential 4.5V), Li 3 PO 4 (lithium deintercalation potential exceeding 4V). These lithium-rich materials 10 have a relatively high capacity, but the lithium deintercalation of these lithium-rich materials 10 requires a relatively high charging voltage, and there is a technical problem of a high plateau voltage. At the same time, the relatively high voltage also causes oxygen to be generated during the first charge and discharge of the lithium supplement material in the lithium-ion battery, and the generated oxygen further oxidizes to cause the electrolyte to oxidize and decompose, thereby reducing the safety and performance of the lithium-ion battery. These lithium supplement materials with a relatively high voltage plateau are also difficult to be compounded with conventional cathode materials (such as the lithium deintercalation potential of lithium iron phosphate is about 3.5V), which limits the wide application of the lithium supplement material.
[0056] In one embodiment, the above-mentioned lithium-rich material 10 can be undoped or doped and modified, or can be surface-coated, pre-lithiated, etc. In the embodiments of the present application, when the lithium-rich material 10 is used as a cathode active material, the lithium-rich material 10 can also be a combination of the above-listed lithium-rich material 10 and conventional cathode materials such as lithium iron phosphate and ternary cathode materials.
[0057] In one embodiment, the functional material 20 may have a conductive function and a catalytic function, so the functional material 20 may be used to improve the conductivity of the lithium-rich material 10 and reduce the delithiation potential of the lithium-rich material 10. In a specific embodiment, the functional material 20 includes one or more of a carbon material 21, an inorganic metal compound material, an organic polymer conductive material, and a semiconductor material. It should be noted that the functional material 20 may be a composite material including multiple materials in order to achieve the above functions.
[0058] It can be understood that the present application utilizes the catalytic function of the functional material 20 to effectively reduce the charging voltage platform of the lithium-rich material 10, thereby improving the utilization rate of some of the above-mentioned lithium-rich materials 10 with higher charging voltages; in addition, the conductive function of the functional material 20 is also utilized to improve the conductivity of the composite lithium-supplementing material, thereby improving the transmission efficiency of ions and electrons, so that the capacity of the lithium-rich material 10 can be fully released.
[0059] In one implementation, please refer to Figure 1 The combination of the lithium-rich material 10 and the functional material 20 may include that a plurality of functional materials 20 are connected to the outer surface of the lithium-rich material 10. Specifically, any particle of the composite lithium-supplementing material includes at least one particle of the lithium-rich material 10 and a plurality of particles of the functional material 20, and the particles of the plurality of functional materials 20 surround the particles of the lithium-rich material 10.
[0060] In one implementation, please refer to Figure 2 The combination of the lithium-rich material 10 and the functional material 20 may also include that the functional material 20 is filled between particles of the lithium-rich material 10. Specifically, in any particle of the composite lithium-supplementing material, there are multiple particles of the lithium-rich material 10 and at least one particle of the functional material 20, and the multiple lithium-rich materials 10 are connected to form secondary particles, and there are gaps between the particles, and the functional material 20 is filled in the gaps.
[0061] In one implementation, please refer to Figure 1 and Figure 2 , the functional material 20 includes a carbon material 21 and a catalyst 22, the surface of the carbon material 21 has a first modified ligand, and the catalyst 22 is connected to the first modified ligand to form a complex. Specifically, the carbon material 21 can provide a conductive function, and the catalyst 22 can provide a catalytic function. The surface of the carbon material 21 has a first modified ligand, that is, one end of the first modified ligand is connected to the carbon material 21, and the other end is connected to the catalyst 22. Thus, a complex is also formed between the first modified complex and the catalyst 22 to achieve a stable connection with the carbon material 21 and the catalyst 22. In addition, the agglomeration of the catalyst 22 itself is prevented, and effective contact is formed to exert a catalytic effect.
[0062] It should be explained that in order to pursue catalytic activity, most catalysts 22 in the prior art will reduce the particle size of the catalyst 22 as much as possible so that the catalyst 22 can fully exert its catalytic effect. However, reducing the particle size of the catalyst 22 is more likely to cause the catalyst 22 to agglomerate to form secondary particles, resulting in uncontrollable particle size of the catalyst 22. In addition, when the catalyst 22 is mixed with the lithium-rich material 10 or added to the positive electrode slurry, since the lithium-rich material 10 itself may have a larger particle size or easy to agglomerate, it will cause the catalyst 22 to further agglomerate, thereby seriously affecting the coating effect of the slurry. Therefore, how to control the catalyst 22, reduce the agglomeration of the catalyst 22, and maximize the catalytic effect has become the key.
[0063] In the present application, the carbon material 21 with the first modified ligand is compounded with the catalyst 22, and the first modified ligand is connected to the surface of the catalytic material, so that the first modified ligand can be combined with the catalyst 22 to form a complex, reduce the agglomeration of the catalyst 22, and maximize the catalytic effect, thereby effectively reducing the charging voltage platform of the lithium supplement. At the same time, the integrated carbon material 21 and the catalyst 22 are evenly dispersed or loaded on the surface of the lithium supplement, which can enhance the interfacial bonding force between the functional material 20 and the lithium-rich material 10. The first modified ligand on the surface of the carbon material 21 can also serve as an active site to promote chemical bonding with the lithium-rich material 10, which helps to improve the stability and electrochemical performance of the composite lithium supplement. The carbon material 21 can also improve the electronic conductivity of the lithium-rich material 10 and promote the rapid transmission of lithium ions.
[0064] In one embodiment, the first modified ligand can be connected to the carbon material 21 through π-π stacking, covalent bonds or hydrogen bond interactions; the first modified ligand can provide oxygen atoms, nitrogen atoms, phosphorus atoms, etc., so the first modified ligand can form a coordination bond connection with the metal ions of the catalyst 22 through the above atoms.
[0065] In one embodiment, the surface of the lithium-rich material 10 has a second modified ligand, and the first modified ligand and the second modified ligand cooperate to connect the lithium-rich material 10 and the carbon material 21. Specifically, the second modified ligand can be a functional group ligand, and the chemical formula of the lithium-rich material 10 having the second modified ligand includes Li x1 C y1 O z1 -COOR1 and / or Li x1 C y1 O z1 -CO-NH-R2, wherein R1 includes an alkyl group or other non-hydrogen group, and R2 includes an alkane or other substituent, such as a methyl group (-CH 3 ), ethyl (-CH 2 CH 3 ), propyl, butyl, phenyl (-C6 H 5 ), halogenated hydrocarbon (-CH 2 Cl, -CH 2 CH 2 F, -CH 2 CH 2 CH 2 Br) etc. In other embodiments, the chemical formula may also include Li x2 M y2 O z2 -COOR1 and / or Li x2 M y2 O z2 -CO-NH-R2, etc. Optionally, the first modifying ligand and the second modifying ligand may be the same.
[0066] It needs to be explained that the second modified ligand on the surface of the lithium-rich material 10 has two functions. On the one hand, it is to facilitate the agglomeration of the lithium-rich materials 10, because the second modified ligand between the lithium-rich materials 10 forms a steric hindrance and can provide charges to form hydrogen bonds, etc., thereby making it difficult for the particles of the lithium-rich material 10 to connect, and also reducing the electrostatic effect between the particles of the lithium-rich material 10, avoiding particle agglomeration to achieve the effect of limiting the particle size of the lithium-rich material 10; on the other hand, it is to improve the conductivity by connecting with the functional material 20 (especially the carbon material 21), because the first modified ligand and the second modified ligand can form hydrogen bonds, thereby increasing the transmission speed of ions and electrons, thereby improving the conductivity, and because the catalyst 22 is also fully dispersed under the action of the first modified ligand, the catalyst 22 can provide a better catalytic effect.
[0067] Therefore, in the present application, a second modified ligand is combined with the lithium-rich material 10, and the second modified ligand is used to limit the agglomeration of the lithium-rich material 10, so that the particle size of the lithium-rich material 10 can be controlled within an appropriate range, thereby improving the performance of the lithium-rich material 10; at the same time, the carbon material 21 with the first modified ligand is composited with the lithium-rich material 10 with the second modified ligand, and the first modified ligand is connected to the surface of the catalytic material, so that the first modified ligand can be combined with the catalyst 22 to form a complex, promote chemical bonding with the lithium-rich material 10, help to improve the stability and electrochemical properties of the composite lithium-supplementing material, and promote the rapid transmission of lithium ions.
[0068] In one embodiment, the first modified ligand may include a first functional group ligand, and the first functional group ligand includes one or more of a carboxyl group, a hydroxyl group, and an amine group. Specifically, the provided carbon material 21 originally has some functional group ligands, which may specifically be oxygen-containing functional groups, such as graphene oxide, etc. Alternatively, the carbon material 21 may be subjected to surface modification treatment so that the surface of the carbon material 21 can have abundant functional group ligands.
[0069] In one embodiment, the first modified ligand may include a non-carbon heteroatom ligand. The non-carbon heteroatom ligand may include a non-metallic heteroatom ligand and / or a metal heteroatom ligand. The non-metallic heteroatom ligand includes one or more of a phosphorus atom, a sulfur atom, and a nitrogen atom. The metal heteroatom ligand may include at least one of a molybdenum atom, a cobalt atom, and a manganese atom.
[0070] In one embodiment, the non-metallic heteroatom ligand can be chemically bonded to the carbon atoms in the carbon material 21 to form a single bond, a double bond, or a triple bond. Doping with the non-metallic heteroatom ligand can improve the conductivity of the carbon material 21, and can make the carbon material 21 catalytic, thereby improving the overall performance of the carbon material 21. In addition, doping the carbon material 21 with the non-metallic heteroatom ligand can also increase the surface active sites of the carbon material 21, so that the catalyst 22 can be connected with the non-metallic heteroatom ligand to form a complex.
[0071] In one embodiment, doping with metal heteroatom ligands can improve the conductivity of the carbon material 21, while improving the stability of the carbon material 21 in the ORR reaction (redox reaction) and providing more active sites, so that the catalyst 22 can be connected with the metal heteroatom ligand to form a complex.
[0072] In one embodiment, the second modified ligand may include a second functional group ligand, and the second functional group ligand includes an ester group -COOR1 and / or an amide group -CO-NH-R2, wherein R1 includes an alkyl group or other non-hydrogen group, and R2 includes an alkane or other substituent.
[0073] In one embodiment, the particle size D50 of the carbon material 21 is 0.5 μm to 1.0 μm. Optionally, the particle size D50 of the carbon material 21 can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, or 1.0 μm. Meeting the particle size of the carbon material 21 within the above range is conducive to controlling the overall particle size of the composite lithium supplement material, and enabling the carbon material 21 to better fit with the catalyst 22 to form a ligand.
[0074] In one embodiment, the tap density of the carbon material 21 is 1.5 g / cm 3 ~3.0g / cm 3 Optionally, the tap density of the carbon material 21 may be 1.5 g / cm 3 , 1.8g / cm 3 , 2g / cm 3 , 2.3g / cm 3 , 2.5g / cm 3 , 2.7g / cm 3 、3.0g / cm 3The tap density of the carbon material 21 being within the above range is conducive to its composite with the catalyst 22 and the lithium-rich material 10, so that the three form a tightly connected composite lithium-supplementing material, and thus the overall particle size of the composite lithium-supplementing material can be controlled.
[0075] In one embodiment, the particle size D50 of the catalyst 22 is 0.2 μm to 1.2 μm. Optionally, the particle size D50 of the catalyst 22 can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm. Meeting the particle size of the catalyst 22 within the above range is conducive to controlling the overall particle size of the composite lithium supplement material, and enabling the carbon material 21 to better fit the catalyst 22 to form a ligand.
[0076] In one embodiment, the tap density of the catalyst 22 is 1.0 g / cm 3 ~4.5g / cm 3 Optionally, the tap density of the catalyst 22 may be 1 g / cm 3 , 1.5g / cm 3 , 2g / cm 3 , 2.5g / cm 3 , 3g / cm 3 , 3.5g / cm 3 , 4g / cm 3 , 4.5g / cm 3 The tap density of the catalyst 22 being within the above range is conducive to its composite with the carbon material 21 and the lithium-rich material 10, so that the three form a tightly connected composite lithium-supplementing material, and thus the overall particle size of the composite lithium-supplementing material can be controlled.
[0077] In one embodiment, the carbon material 21 includes one or more of Ketjen black (KB), carbon black (SP), carbon nanotubes (CNTs), and carbon fibers (CNFs).
[0078] In one embodiment, the catalyst 22 includes one or more of metal oxides, metal carbides, and metal sulfides. In a specific embodiment, the catalyst 22 includes WO 3 、MoO 2 、Co 3 O 4 、CoO、Nb 2 O 5 At least one of the above.
[0079] In one embodiment, the particle size D50 of the lithium-rich material 10 is 0.05 μm to 1.2 μm. Optionally, the particle size D50 of the lithium-rich material 10 can be 0.05 μm, 0.1 μm, 0.2 μm, 0.4 μm, 0.6 μm, 0.8 μm, 1 μm, or 1.2 μm. When the particle size D50 of the lithium-rich material 10 is within the above range, the particle size distribution of the composite lithium-supplementing material can be controlled, the electrochemical performance can be optimized, and the catalytic effect of the functional material 20 on the lithium-rich material 10 can be ensured, and the release efficiency of lithium ions can be improved. When the particle size of the lithium-rich material 10 is too small, the lithium-rich material 10 is severely agglomerated and is not easy to fully combine with the functional material 20. When the particle size of the lithium-rich material 10 is too large, the catalytic effect of the functional material 20 on the lithium-rich material 10 is reduced, and the fineness of the resulting slurry is affected, thereby affecting the coating effect.
[0080] In one embodiment, the tap density of the lithium-rich material 10 is 1.0 g / cm 3 ~8.5g / cm 3 Optionally, the tap density of the lithium-rich material 10 may be 1 g / cm 3 , 2g / cm 3 , 3g / cm 3 , 4g / cm 3 , 5g / cm 3 , 6g / cm 3 , 7g / cm 3 , 8g / cm 3 、8.5g / cm 3 The tap density of the lithium-rich material 10 being within the above range is conducive to its composite with the functional material 20, so that the two form a tightly connected composite lithium-supplementing material, and thus the overall particle size of the composite lithium-supplementing material can be controlled.
[0081] In one embodiment, the mass fraction of the functional material 20 in the composite lithium-supplementing material is 5% to 30%. Optionally, the mass fraction of the functional material 20 in the composite lithium-supplementing material is 5wt%, 10wt%, 12wt%, 14wt%, 16wt%, 18wt%, 20wt%, 22wt%, 24wt%, 26wt%, 28wt%, 30wt%. When the mass fraction of the functional material 20 in the composite lithium-supplementing material is within the above range, the catalytic effect of the functional material 20 on the lithium-rich material 10 can be ensured, and the lithium ion capacity of the composite lithium-supplementing material can be met. When the mass fraction of the functional material 20 in the composite lithium-supplementing material is too small, the functional material 20 is too small, resulting in poor catalytic effect, and the lithium release voltage of the lithium-rich material 10 is limited. When the mass fraction of the functional material 20 in the composite lithium-supplementing material is too large, there is too much functional material 20 and it does not contribute lithium ions, resulting in a decrease in lithium capacity.
[0082] In one embodiment, the particle size D50 and particle size D99 of the composite lithium supplement material respectively satisfy: 0.5μm≤D50≤2μm, D99≤15μm. Optionally, the particle size D50 of the composite lithium supplement material may be 0.6μm, 0.8μm, 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2μm; the particle size D99 of the composite lithium supplement material may be less than any one of 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm.
[0083] The present application controls the particle size D50 and particle size D99 of the composite lithium supplement material within the above range, thereby controlling the overall particle size distribution of the composite lithium supplement material, and optimizing the electrochemical properties of the composite lithium supplement material. The composite lithium supplement material is more evenly coated during application, thereby greatly reducing the tortuosity of the electrode sheet, which is beneficial to improving the rate and cycle performance of the material.
[0084] This application provides a method for preparing a composite lithium supplement material. Figure 3 and Figure 4 .
[0085] In one embodiment, the preparation method of the composite lithium supplement material is as follows: Figure 3 , specifically including the following steps:
[0086] Step S11, mixing the lithium-rich material and the functional material together to obtain a mixed solution, wherein the surface of at least one of the lithium-rich material and the functional material has a modified ligand.
[0087] Step S12, adding the mixed solution into an organic solvent and stirring to precipitate a solid, washing and drying the solid to obtain a composite lithium supplementing material, wherein the lithium-rich material and the functional material are connected via a modified ligand.
[0088] In one embodiment, in step S11, the lithium-rich material and the functional material are mixed together, specifically comprising: dissolving the lithium-rich material, the functional material and the dispersant in a solvent, and obtaining a mixed solution after sufficient stirring. The solvent may be deionized water; and the mass proportion of the dispersant in the mixed solution is 0.1% to 1%.
[0089] In one embodiment, in step S12, the mixed liquid is added to the organic solvent and stirred to precipitate the solid, specifically comprising: slowly adding the mixed liquid to the organic solvent, and stirring sufficiently to precipitate the solid. The organic solvent comprises one or more of methanol, ethanol, xylene, n-hexane, isopropanol, and N-methylpyrrolidone; the mixed liquid is added to the organic solvent at a liquid inlet speed of 0.5 ml / min to 5 ml / min; and the stirring speed is 200 rpm to 600 rpm.
[0090] In one embodiment, the preparation method of the functional material is as follows Figure 4 , specifically including the following steps:
[0091] Step S01, using a surface modifier to perform surface modification on a carbon material to obtain a carbon material having a first modified ligand.
[0092] Step S02, mixing the carbon material with the first modified ligand and the catalyst for reaction, and washing and drying after the reaction to obtain a functional material.
[0093] In one embodiment, in step S01, the surface of the carbon material is modified using a surface modifier, specifically comprising: firstly oxidizing the carbon material with an oxidant, and then modifying the surface of the carbon material with a surface modifier. The oxidant includes one or more of nitric acid, hydrochloric acid, sulfuric acid, and sulfuric acid; the concentration of the oxidant is 0.5 mol / L to 8 mol / L; the surface modifier includes one or more of ethylenediamine, sodium alkylbenzene sulfonate (ABS), dodecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, etc.
[0094] In one embodiment, in step S02, the carbon material with the first modified ligand and the catalyst are mixed and reacted, specifically comprising: adding the catalyst to the solution of the carbon material, and then stirring for a period of time at a certain temperature to allow the two to react fully. The reaction temperature is 40°C to 60°C; the reaction time is 1h to 6h; and the stirring speed is 400rpm to 800rpm.
[0095] In one embodiment, the preparation method of lithium-rich material is as follows Figure 5 , specifically including the following steps:
[0096] Step S21, mixing a functionalizing agent and a lithium-rich material in a solvent for reaction to obtain a functionalized lithium-rich material.
[0097] Step S22, mixing the catalyst, the organic modifier and the functionalized lithium-rich material to react, to obtain a lithium-rich material having a second modified ligand on the surface.
[0098] In one embodiment, in step S21, the purpose of mixing the functionalizing agent with the lithium-rich material is to introduce functional groups on the lithium-rich material so as to facilitate the subsequent esterification / amidation reaction on the surface of the lithium-rich material. Among them, the functional group chemical reagent may include one or more of silane coupling agents, alcohols, carboxylic acids, oleic acid, carbamates, propionamide, etc. The solvent may include one or more of methanol, ethanol, tetrahydrofuran, ether, ethyl acetate, etc. The reaction temperature is 60°C to 100°C, and the reaction time is 1h to 6h.
[0099] In one embodiment, in step S22, the catalyst may be one or more of sulfuric acid, p-toluenesulfonic acid, etc.; and the reaction temperature is 60°C to 150°C.
[0100] The present application provides a positive electrode material.
[0101] In one embodiment, the positive electrode material includes a positive electrode active material and a composite lithium supplement material. The composite lithium supplement material is the composite lithium supplement material provided in the above embodiment. Optionally, the positive electrode active material can be a phosphate positive electrode active material or a ternary positive electrode active material. In a specific embodiment, the positive electrode active material includes one or more of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium vanadium oxyphosphate, lithium fluorinated vanadium phosphate, lithium titanate, lithium nickel cobalt manganese oxide, and lithium nickel cobalt aluminum oxide.
[0102] In one embodiment, the content of the composite lithium-supplementing material in the positive electrode material can be controlled at 1% to 6% of the mass of the positive electrode active material. This ratio can just make up for the loss of active lithium in the battery during the first charging process. If the amount of composite lithium-supplementing material added to the positive electrode material is too low, the active lithium lost in the positive electrode active material cannot be fully replenished, which is not conducive to improving the energy density and capacity retention rate of the battery. If the amount of composite lithium-supplementing material added to the positive electrode active material is too high, the original reversible capacity will be occupied and the cost will be increased. In some specific embodiments, in the positive electrode material, the mass percentage of the composite lithium-supplementing material can be 1%, 2%, 4%, 6%, etc.
[0103] In one embodiment, the slurry fineness of the positive electrode material is 5μm to 15μm. Specifically, the slurry fineness of the positive electrode material includes not only the composite lithium supplement material, but also the positive electrode active material, conductive agent, adhesive, etc. in the positive electrode material. The slurry fineness of the positive electrode material is within the above range, so that the slurry particle size distribution of the positive electrode material is uniform and the slurry fineness is appropriate, so that the active material layer coated with the slurry is more uniform and dense, and the coating has lower pores and defects, which can reduce the tortuosity of the pole piece, thereby helping to improve the ion transmission efficiency and performance of the battery. Optionally, the slurry fineness of the positive electrode material can be 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm.
[0104] In one embodiment, the present application further provides a positive electrode plate, the positive electrode plate includes a current collector and an active material layer disposed on the current collector, the active material layer includes the composite lithium supplement material of any one of the above embodiments. Or the active material layer includes the composite lithium supplement material obtained by the preparation method of the composite lithium supplement material in the above embodiments.
[0105] In one embodiment, the positive electrode sheet includes a positive current collector, and the positive current collector has a positive active layer, and the positive active layer includes components such as positive active materials, composite lithium supplement materials, conductive agents, and binders. The present application does not specifically limit these materials, and suitable materials can be selected according to actual application requirements. The positive current collector includes but is not limited to any one of copper foil and aluminum foil. The conductive agent includes one or more of graphite, carbon black, acetylene black, graphene, carbon fiber, C60 and carbon nanotubes, and the content of the conductive agent in the positive active layer is 3wt% to 5wt%. The types of binders include polyvinylidene chloride, soluble polytetrafluoroethylene, styrene-butadiene rubber, hydroxypropyl methylcellulose, methylcellulose, carboxymethyl cellulose, polyvinyl alcohol, acrylonitrile copolymer, sodium alginate, chitosan and chitosan derivatives, and the content of the binder in the positive active layer is 2wt% to 4wt%.
[0106] In one embodiment, the positive electrode sheet has a porosity of 30% to 45%. Specifically, the porosity of the positive electrode sheet is affected by the composite lithium supplement material provided in the above embodiment, and the sheet porosity helps the electrolyte to infiltrate, improves the lithium ion conductivity, and thus improves the battery performance; and the appropriate porosity can increase the effective reaction area of the electrode and improve the battery capacity. Optionally, the positive electrode sheet porosity can be 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 45%.
[0107] In one embodiment, the tortuosity of the positive electrode sheet is 1 to 2.5. When the tortuosity of the positive electrode sheet is within the above range, the migration speed and efficiency of ions in the sheet can be ensured, thereby improving battery performance. Optionally, the tortuosity of the positive electrode sheet can be 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.5.
[0108] In one embodiment, the powder removal rate of the positive electrode sheet is less than or equal to 0.02%. Optionally, the powder removal rate of the positive electrode sheet can be 0%, 0.01%, 0.02%; the powder removal rate of the positive electrode sheet can range from 0% to 0.02%, 0% to 0.01%, 0.01% to 0.02%.
[0109] In one embodiment, the positive electrode sheet peel strength is greater than or equal to 6N / 10mm. Optionally, the positive electrode sheet peel strength may be 6N / 10mm, 7N / 10mm, 8N / 10mm, 9N / 10mm, or 10N / 10mm.
[0110] In one embodiment, the present application also provides a secondary battery, which includes a negative electrode, a positive electrode and an electrolyte, wherein the positive electrode includes the above-mentioned positive electrode material; the electrolyte can be an electrolyte solution, so the secondary battery also includes a diaphragm arranged between the positive electrode plate and the negative electrode plate; or, the electrolyte can be a solid electrolyte solution, so the secondary battery does not have a diaphragm and is replaced by a solid electrolyte.
[0111] The technical solution of the present application is described in detail below through specific embodiments.
[0112] Example 1
[0113] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The composite lithium supplement material includes a lithium-rich material (Li 2 CO 3 ) and functional materials, including carbon materials (CNTs) and catalysts (NH 2 -Co 3 O 4 ). Among them, NH 2 Connected to the carbon material, and NH 2 With Co 3 O 4 Form a complex.
[0114] The particle size D50 of the composite lithium supplement material is 1 μm, the particle size D99 of the composite lithium supplement material is 7.3 μm, the particle size D50 of the carbon material is 0.7 μm, the particle size D50 of the catalyst is 0.6 μm, and the particle size D50 of the lithium-rich material is 0.6 μm. The mass fraction of the functional material in the composite lithium supplement material is 10%.
[0115] The preparation method of the composite lithium supplement material comprises the following steps:
[0116] 1) Use 1 mol / L nitric acid to oxidize CNTs first, then add ethylenediamine, stir for 2 hours, and then add Co 3 O 4 , reacted at 50 °C and 600 rpm for 2 h to obtain the functional material (NH 2 -Co 3 O 4 / CNTs).
[0117] 2) 5g of Li 2 CO 3 , 10wt% NH 2 -Co 3 O 4 / CNTs and 0.2wt% PVP were fully dissolved in water, and then added into ethanol at an injection rate of 3ml / min and stirred; after washing and drying, the composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs.
[0118] Example 2
[0119] This embodiment provides a composite lithium supplement material Li 2 CO 3 / P x -Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the carbon material is doped with P atoms, and P x With Co 3 O 4 The particle size D50 of the composite lithium supplement material is 1.3 μm, the particle size D99 of the composite lithium supplement material is 9.2 μm, and the particle size D50 of the catalyst is 0.68 μm.
[0120] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 1), 1 mol / L nitric acid is used to first oxidize the CNTs, and then trioctylphosphine is added, stirred for 2 h, and then Co is added. 3 O 4 , reacted at 60°C and 800 rpm for 6 h to obtain the functional material Li 2 CO 3 / P x -Co 3 O 4 / CNTs.
[0121] Example 3
[0122] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the particle size D50 of the composite lithium supplement material is 0.47 μm, the particle size D99 of the composite lithium supplement material is 5.2 μm, and the particle size D50 of the carbon material is 0.38 μm.
[0123] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the concentration of the CNTs treated with nitric acid in step 1) is changed to 0.4 mol / L.
[0124] Example 4
[0125] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the particle size D50 of the composite lithium supplement material is 2.4 μm, the particle size D99 of the composite lithium supplement material is 14.4 μm, and the particle size D50 of the carbon material is 1.19 μm.
[0126] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the concentration of the nitric acid used to treat the CNTs in step 1) is changed to 8 mol / L.
[0127] Example 5
[0128] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the particle size D50 of the composite lithium supplement material is 1.2 μm, the particle size D99 of the composite lithium supplement material is 8.8 μm, and the particle size D50 of the catalyst is 0.18 μm.
[0129] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the reaction temperature and time in step 1) are changed to 40° C. and 1 h.
[0130] Example 6
[0131] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the particle size D50 of the composite lithium supplement material is 1.98 μm, the particle size D99 of the composite lithium supplement material is 13.3 μm, and the particle size D50 of the catalyst is 1.32 μm.
[0132] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the reaction temperature and time in step 1) are changed to 60° C. and 6 h.
[0133] Example 7
[0134] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium-supplementing material and the composite lithium-supplementing material provided in Example 1 is that the particle size D50 of the composite lithium-supplementing material is 0.8 μm, the particle size D99 of the composite lithium-supplementing material is 6.6 μm, and the particle size D50 of the lithium-rich material is 0.047 μm.
[0135] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the rate of entering into ethanol in step 2) is changed to 5.5 ml / min.
[0136] Example 8
[0137] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium-supplementing material and the composite lithium-supplementing material provided in Example 1 is that the particle size D50 of the composite lithium-supplementing material is 2.34 μm, the particle size D99 of the composite lithium-supplementing material is 14.1 μm, and the particle size D50 of the lithium-rich material is 1.31 μm.
[0138] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that the rate of entering into ethanol in step 2) is changed to 0.45 ml / min.
[0139] Example 9
[0140] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the particle size D50 of the composite lithium supplement material is 0.97 μm, the particle size D99 of the composite lithium supplement material is 16.2 μm, and the mass fraction of the functional material in the composite lithium supplement material is 1%.
[0141] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 2), 5 g of Li 2 CO 3 , 1wt% NH 2 -Co 3 O 4 @CNTs and 0.2wt% PVP are fully dissolved in water.
[0142] Example 10
[0143] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the particle size D50 of the composite lithium supplement material is 1.85 μm, the particle size D99 of the composite lithium supplement material is 17.4 μm, and the mass fraction of the functional material in the composite lithium supplement material is 50%.
[0144] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that in step 2), 5 g of Li 2 CO 3 , 50wt%NH 2 -Co 3 O 4 @CNTs and 0.2wt% PVP are fully dissolved in water.
[0145] Embodiment 11
[0146] This embodiment provides a composite lithium supplement material Li 2 C 2 O 4 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium-supplementing material and the composite lithium-supplementing material provided in Example 1 is that the lithium-rich material is Li 2 C 2 O 4 The particle size D50 of the composite lithium-supplementing material is 1.89 μm, the particle size D99 of the composite lithium-supplementing material is 12.1 μm, and the particle size D50 of the lithium-rich material is 1.28 μm.
[0147] The preparation method of the composite current collector is the same as the preparation method provided in Example 1.
[0148] Example 12
[0149] This embodiment provides a composite lithium supplement material Li 2 CO 3 / NH 2 -MoO 2 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the catalyst is MoO 2 The particle size D50 of the composite lithium supplement material is 1.25 μm, the particle size D99 of the composite lithium supplement material is 9.0 μm, and the particle size D50 of the catalyst is 0.83 μm.
[0150] The preparation method of the composite current collector is the same as the preparation method provided in Example 1.
[0151] Embodiment 13
[0152] This comparative example provides a composite lithium supplement material Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the particle size D50 of the composite lithium supplement material is 2.45 μm, and the particle size D99 of the composite lithium supplement material is 20 μm.
[0153] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that 0.2 wt % of PVP is not added.
[0154] Embodiment 14
[0155] This embodiment provides a composite lithium supplement material COOCH 3 -Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs. The composite lithium supplement material includes a lithium-rich material (COOCH 3 -Li 2 CO 3 ) and functional materials, including carbon materials (CNTs) and catalysts (NH 2 -Co 3 O 4 ). Among them, NH 2 Connected to the carbon material, and NH 2 With COOCH 3 -Li 2 CO 3 Forming a ligand complex.
[0156] The particle size D50 of the composite lithium supplement material is 1 μm, the particle size D99 of the composite lithium supplement material is 7.3 μm, the particle size D50 of the carbon material is 0.7 μm, the particle size D50 of the catalyst is 0.6 μm, and the particle size D50 of the lithium-rich material is 0.6 μm. The mass fraction of the functional material in the composite lithium supplement material is 10%.
[0157] The preparation method of the composite lithium supplement material comprises the following steps:
[0158] 1) Use 1 mol / L nitric acid to oxidize CNTs first, then add ethylenediamine, stir for 2 hours, and then add Co3 O 4 , reacted at 50 °C and 600 rpm for 2 h to obtain the functional material (NH 2 -Co 3 O 4 / CNTs).
[0159] 2) Oleic acid and Li 2 CO 3 Dissolve in ethyl acetate, mix well, and react at 75°C for 4 hours to obtain a functionalized lithium-rich material Li 2 CO 3 .
[0160] 3) Sulfuric acid and the functionalized lithium-rich material are dissolved in methanol and subjected to rotary evaporation at 65°C to obtain a lithium-rich material COOCH having a second modified ligand on the surface. 3 -Li 2 CO 3 .
[0161] 4) 5g of COOCH 3 -Li 2 CO 3 , 10wt% NH 2 -Co 3 O 4 / CNTs and 0.2wt% PVP were fully dissolved in water, and then added into ethanol at an injection rate of 3ml / min and stirred; after washing and drying, the composite lithium supplement material COOCH 3 -Li 2 CO 3 / NH 2 -Co 3 O 4 / CNTs.
[0162] Comparative Example 1
[0163] This embodiment provides a composite lithium supplement material Li 2 CO 3 / Co 3 O 4 / CNTs. The difference between the composite lithium supplement material and the composite lithium supplement material provided in Example 1 is that the carbon material and the catalyst are simply mixed, the particle size D50 of the composite lithium supplement material is 3.2 μm, and the particle size D99 of the composite lithium supplement material is 28.7 μm.
[0164] The difference between the preparation method of the composite current collector and the preparation method provided in Example 1 is that there is no step 1).
[0165] Step 2): 5 g of Li 2 CO 3, 10wt%Co 3 O 4 +CNTs and 0.2wt% PVP were fully dissolved in water, and added into ethanol at an injection rate of 3ml / min and stirred; after washing and drying, the composite lithium supplement material Li 2 CO 3 / Co 3 O 4 / CNTs.
[0166] The parameters of the composite lithium supplement materials provided by Examples 1 to 14 and Comparative Example 1 are shown in Table 1:
[0167] Table 1 Parameters of composite lithium supplement materials provided in Examples and Comparative Examples
[0168]
[0169]
[0170] The composite lithium supplement materials provided in the above-mentioned Examples 1 to 14 and the composite lithium supplement materials provided in Comparative Example 1 are respectively assembled into positive electrode sheets and lithium-ion batteries according to the following methods:
[0171] Positive electrode sheet: The composite lithium supplement material, SP and PVDF are mixed in a mass ratio of 90:4:6 to form a positive electrode slurry, the positive electrode slurry is coated on the surface of aluminum foil, vacuum dried at 110°C overnight, and rolled to obtain a positive electrode sheet;
[0172] Negative electrode: lithium sheet;
[0173] Electrolyte: Ethylene carbonate and ethyl methyl carbonate were mixed in a volume ratio of 3:7, and LiPF was added 6 , forming an electrolyte, LiPF 6 The concentration is 1 mol / L;
[0174] Diaphragm: Polypropylene microporous separator;
[0175] Lithium-ion battery assembly: Assemble button-type lithium-ion full batteries in an inert atmosphere glove box in the order of negative electrode sheet - separator - electrolyte - positive electrode sheet.
[0176] The materials and batteries provided in Examples 1 to 14 and Comparative Example 1 were tested as follows:
[0177] 1) The slurry fineness test of the positive electrode slurry includes the following steps: placing a thoroughly cleaned and dried scraper on a flat, horizontal, non-slip surface; dropping enough positive electrode slurry sample into the deepest part of the scraper groove, i.e. the part with the maximum scale value, and allowing the sample to overflow slightly; pinching the scraper with the thumb and index finger of both hands, placing the scraper blade horizontally at the part with the maximum scale value of the scraper (at the edge of the sample), making the long side of the scraper parallel to the wide side of the scraper and in vertical contact with the scraper surface. Then pull the slurry across the entire length of the groove at an appropriate speed; observe the depth of the uniformly exposed particles in the groove along the direction of the incident light at an angle of 30°, and use this thickness to represent the slurry fineness.
[0178] 2) Porosity detection of positive electrode sheet: the detection steps include: taking a photo of the cross section of the battery electrode sheet by scanning electron microscope to obtain a monochrome grayscale coating cross section image. Then, the image is processed and analyzed by image processing software, and a threshold is obtained based on the obvious grayscale difference between the pores and coating particles in the coating cross section image, and the two areas are segmented and marked based on the threshold to obtain the particle area and the pore area. Finally, the ratio of the number of pixels in the pore area to the total number of pixels in the coating cross section image is counted, which is the porosity of the coating cross section.
[0179] 3) Detection of the tortuosity of the positive electrode sheet. The detection steps include: by measuring the electrochemical impedance spectrum of the battery, the ion transfer resistance of the electrode can be obtained, and then the tortuosity can be evaluated. The Nyquist diagram of the electrochemical impedance spectrum has the shape characteristics of the intersection of the low-frequency area segment and the high-frequency area segment. The low-frequency segment in the Nyquist diagram is extended to intersect with the X-axis. The difference between the intersection point and the intersection point of the high-frequency segment and the X-axis is 3 times the ionic impedance of the electrode coating; Substituting the ionic impedance into the formula τ=(R ion .Aεσ.) / d, combined with the parameters such as the electrode area, porosity, electrolyte conductivity and electrode thickness, the tortuosity of the electrode can be calculated. In the formula, τ is the tortuosity; R ion is the ionic resistance; A is the electrode area; ε is the electrode porosity; σ is the electrolyte conductivity; d is the thickness of the electrode.
[0180] 4) Electrochemical performance test of lithium-ion battery, the test conditions are as follows: charge at a rate of 0.1C, with a cut-off voltage of 4.7V; constant voltage charge at a cut-off of 4.7V; after the charging process is completed, stand for 10 minutes and discharge at a rate of 0.1C, with a cut-off voltage of 2.5V; observe the charging platform during the charging process to obtain the charging voltage platform of the composite lithium supplement material; and the first cycle efficiency = (charge specific capacity / discharge specific capacity)*100%.
[0181] The test results of 1)-4) above are shown in Table 2 below:
[0182] Table 2. Test results of embodiments and comparative examples
[0183]
[0184] From the test results of Examples 1-14 and Comparative Example 1 in Table 2, it can be seen that by combining organic ligands on lithium-rich materials and / or functional materials, the particle size of lithium-rich materials and the resulting composite lithium-supplementing materials can be controlled. The fineness of the positive electrode slurry prepared by Examples 1-14 is much smaller than that of the comparative example, and the electrode porosity and electrode tortuosity of the embodiments are also smaller than those of the comparative example. The charging specific capacity of the secondary battery is greater than that of the comparative example, and the charging voltage platform is smaller than that of the comparative example. This shows that the performance of the composite lithium-supplementing material provided by the present application is superior to that of the lithium-supplementing material of the prior art.
[0185] It can be seen from the test results of Example 1 and Example 2 in Table 2 that by combining functional group ligands or heteroatom ligands on the carbon material, the effect of reducing the particle size of the material can be achieved, and the charging specific capacity can be increased and the charging voltage platform can be reduced.
[0186] From the test results of Example 1 and Examples 3-8 in Table 2, it can be seen that the combination of carbon materials and catalysts with different particle sizes will directly affect the particle size of the functional material, thereby changing the particle size of the composite lithium supplement material; at the same time, we can also adjust the particle sizes of the carbon material, catalyst and lithium supplement material respectively through different experimental conditions, so that the synergistic particle size (composite lithium supplement particle size) between the three can be controlled. In addition, only when the particle sizes of the carbon material, catalyst and lithium supplement material are all in the appropriate range, the fineness of the slurry will be less than 15μm, the coated active material layer will be more uniform and dense, the coating will have lower pores and defects, and the tortuosity of the pole piece can be reduced, which helps to improve the ion transmission efficiency and performance of the battery.
[0187] It can be seen from the test results of Example 1 and Examples 9-10 in Table 2 that when the proportion of functional materials is too small (poor catalytic effect) or too much (occupying too much active substance), it will have an adverse effect on the slurry fineness and affect the capacity of the lithium supplement agent; because when the proportion of functional materials is too large or too small during the compounding process, it will make the catalyst easier to agglomerate, resulting in a larger particle size of the composite lithium supplement.
[0188] It can be seen from the test results of Example 1 and Examples 11-12 in Table 2 that changing the types of ligands, catalysts and lithium supplementing materials can achieve the effect of controlling the particle size of the composite lithium supplementing material, and the material has good processability and high capacity.
[0189] From the test results of Example 1 and Example 13 in Table 2, it can be seen that by using carbon materials, catalysts and lithium-rich materials with the same particle size, composite lithium-supplementing materials with different particle sizes can be obtained by adjusting the experimental conditions. The distribution of the particle sizes D50 and D99 of the composite lithium-supplementing materials also affects the slurry fineness and the performance of the pole piece and the battery, indicating that the present application has an advantage over the prior art in controlling the particle size of the composite lithium-supplementing material within an appropriate range.
[0190] It can be seen from the test results of Example 1 and Example 14 in Table 2 that the lithium-rich material and the functional material can have modified ligands at the same time, and when both have modified ligands, the particle size distribution of the material is more uniform, and a smaller material particle size can obtain a battery with better performance.
[0191] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.
[0192] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.
Claims
1. A composite lithium supplement material, characterized in that: The invention comprises a lithium-rich material and a functional material, wherein a surface of at least one of the lithium-rich material and the functional material has a modified ligand, and the lithium-rich material and the functional material are connected via the modified ligand.
2. The composite lithium supplement material according to claim 1, characterized in that: The functional material comprises a carbon material and a catalyst. The surface of the carbon material has a first modified ligand, and the catalyst is connected with the first modified ligand to form a complex.
3. The composite lithium supplement material according to claim 2, characterized in that: The surface of the lithium-rich material has a second modified ligand, and the first modified ligand and the second modified ligand cooperate to connect the lithium-rich material and the carbon material.
4. The composite lithium supplement material according to claim 3, characterized in that: The first modifying ligand includes a first functional group ligand and / or a non-carbon heteroatom ligand, and the second modifying ligand includes a second functional group ligand.
5. The composite lithium supplement material according to claim 4, characterized in that: The first functional group ligand includes one or more of a carboxyl group, a hydroxyl group, and an amine group; the heteroatom ligand includes one or more of a phosphorus atom, a sulfur atom, and a nitrogen atom; the second functional group ligand includes an ester group -COOR1 and / or an amide group -CO-NH-R2, wherein R1 includes an alkyl group or other non-hydrogen group, and R2 includes an alkane or other substituent.
6. The composite lithium supplement material according to any one of claims 2 to 5, characterized in that: The particle size D50 of the carbon material is 0.5 μm to 1.0 μm; and / or The tap density of the carbon material is 1.5 g / cm 3 ~3.0g / cm 3 , and / or The particle size D50 of the catalyst is 0.2 μm to 1.2 μm; and / or The tap density of the catalyst is 1.0 g / cm 3 ~4.5g / cm 3 , and / or The carbon material includes one or more of Ketjen black, carbon black, carbon nanotubes, and carbon fibers; and / or The catalyst includes one or more of metal oxides, metal carbides, and metal sulfides.
7. The composite lithium supplement material according to any one of claims 1 to 6, characterized in that: The particle size D50 of the lithium-rich material is 0.05 μm to 1.2 μm; The tap density of the lithium-rich material is 1.0 g / cm 3 ~8.5g / cm 3 ; and / or The mass fraction of the functional material in the composite lithium supplement material is 5% to 30%; and / or The particle size D50 of the composite lithium supplement material is 0.5 μm to 2 μm; and / or The particle size D99 of the composite lithium supplement material is less than or equal to 15 μm.
8. A method for preparing a composite lithium supplement material, characterized in that: include: Mixing a lithium-rich material and a functional material together to obtain a mixed solution, wherein a surface of at least one of the lithium-rich material and the functional material has a modified ligand; The mixed solution is added into an organic solvent and stirred to precipitate a solid, and the solid is washed and dried to obtain the composite lithium supplement material. The lithium-rich material and the functional material are connected via the modified ligand.
9. The method for preparing the composite lithium supplement material according to claim 8, characterized in that: Before mixing the lithium-rich material with the modified ligand and the functional material together, the method comprises: Using a surface modifier to modify the surface of the carbon material to obtain a carbon material having a first modified ligand; The carbon material having the first modified ligand and a catalyst are mixed for reaction, and after the reaction, the functional material is obtained by washing and drying.
10. A secondary battery, characterized in that: It comprises a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode comprises the composite lithium supplement material according to any one of claims 1 to 7.
11. The secondary battery according to claim 10, characterized in that: The positive electrode has a pole sheet porosity of 30% to 45%, and / or a pole sheet tortuosity of 1 to 2.5; and / or a pole sheet powder shedding rate of less than or equal to 0.02%; and / or a pole sheet peeling strength of greater than or equal to 6N / 10mm.